TI_GERICHTE 52.2021.336 vom 5. August 2021 , Revoca della licenza di condurre a titolo definitivo. Effetto sospensivo - TI Tribunale d'appello (2021)
Revoca della licenza di condurre a titolo definitivo. Effetto sospensivo